Neutrophils Promote Tumor Progression in Oral Squamous Cell Carcinoma by Regulating EMT and JAK2/STAT3 Signaling Through Chemerin - Hu, Xiaoyuan; Xiang, Fenggang; Feng, Yuanyong; Gao, Fei; Ge, Shengyou; Wang, Chengqin; Zhang, Xuan; Wang, Ning (Frontiers in Oncology, 2022)
Oral squamous cell carcinoma (OSCC) is the most common malignancy of the oral cavity. It is reported that in the tumor microenvironment, tumor-associated neutrophils (TANs) can promote tumor growth, invasion, and metastasis. The aim of this study was to explore the relationship between neutrophil infiltration and Chemerin expression on tumor cells, as well as their relationship with clinicopathological parameters and clinical prognosis in 74 cases of Oral squamous cell carcinoma tissues. We also explored the role of the interaction with neutrophils and Chemerin on the functions of OSCC cells (Cal27, SCC9 and SCC15) in vitro. The results showed that Chemerin overexpression in OSCC may increase neutrophil infiltration of tumor tissues. Chemerin overexpression and neutrophil infiltration were prognostic factors of poor clinical outcomes. Furthermore, we found that TANs promote OSCC migration, invasion and proliferation and EMT through Chemerin. TANs activate JAK2/STAT3 signaling through Chemerin, and then up-regulate its downstream signaling target genes, such as Phospho-Rb, E2F1, CyclinE1 and CyclinD1. Taken together, our results revealed that TANs and Chemerin are potentially involved in OSCC progression and metastasis. TANs may promote the JAK2/STAT3 signaling pathway and EMT in OSCC cells through Chemerin.